Fractographic-fractal dimension correlation with crack initiation and fatigue life for notched aluminium alloys under bending load - Macek, Wojciech (2023)
In this study, fatigue fracture surfaces of aluminium alloy 2017-T4 notched specimens were investigated under cyclic bending to find an alternative failure loading index.. The surface topographies were measured on the entire fracture area with an optical profilometer for different loading conditions. Fatigue crack initiation life Ni and total fatigue life Nf were examined using standard surface topography parameters (such as, root mean square height Sq, arithmetical mean height Sa, maximum height Sz) and non-standard surface topography parameters (such as, fractal dimension Df). Fatigue life assessment was successfully performed by combining both fracture surface topography and stress state features. The results show that the fracture plane geometry, expressed by the fractographic-fractal dimension, can facilitate the estimation of post-failure loading history.